Situation Report: Hungary, 23 November 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Head of PPF Says Hungary Should Follow Open Door Policy Party Daily Editorial Emphasizes Renewal and Reform Bishop Draws Balance of "Ad Limina" Visit Losonczi in Kuwait to Shop for More Petrodollars Head of State Office for Religious Affairs Condemns Pacific Views Celebration of Gyula Illyes's 80th Birthday Hungarian Youth and the Communist Youth League Western Experience Helps Greater Yields in Agriculture